Purification, characterization and allergenicity assessment of 26 kDa protein, a major allergen from Cicer arietinum. (June 2016) - Verma, Alok Kumar; Sharma, Akanksha; Kumar, Sandeep; Gupta, Rinkesh Kumar; Kumar, Dinesh; Gupta, Kriti; Giridhar, B.H.; Das, Mukul; Dwivedi, Premendra D.
Graphical abstract: Highlights: A 26 kDa protein from chickpea was purified and characterized as plant albumin. Chickpea 26 kDa protein administration in BALB/c mice induces allergic responses. In vitro study on RBL-2H3 cells showed an enhanced release of allergic mediators when sensitized with the sera of treated mice and challenged with the same 26 kDa chickpea protein. Upregulated expressions of mast cell signaling molecules were observed. Abstract: Chickpea (CP), a legume of the family Fabaceae, is an important nutrient-rich food providing protein, essential amino acids, vitamins, dietary fibre, and minerals. Unfortunately, several IgE-binding proteins in CP have been detected that are responsible for allergic manifestations in sensitized population. Therefore, the prevalence of CP induced allergy prompted us towards purification, characterization and allergenicity assessment of a major ∼26 kDa protein from chickpea crude protein extract (CP-CPE). Purification of CP 26 kDa protein was done using a combination of fractionation and anion exchange chromatography. This protein was further characterized as "Chain A, crystal structure of a plant albumin" from Cicer arietinum with Mol wt 25.8 kDa by Liquid chromatography-tandem mass spectrometry (LC–MS/MS) analysis. Further, allergenic potential of purified 25.8 kDa protein was assessed using in vivo and in vitro model. Purified protein showed IgE-binding capacity with sensitized BALB/c mice and CP allergic patient's sera. Enhanced levels of specific and total IgE, MCP-1, MCPT-1, myeloperoxidase, histamine, prostaglandin D2, and cysteinyl leukotriene were found in sera of mice treated with CP ∼26 kDa protein. Further, expressions of Th2 cytokines (i.e. IL-4, IL-5, IL-13), transcription factors ( i.e. GATA-3, STAT-6, SOCS-3) and mast cell signaling proteins (Lyn, cFgr, Syk, PLC-γ2, PI–3 K, PKC) were also found increased at mRNA and protein levels in the intestines of mice treated with CP ∼26 kDa protein. In addition, enhanced release of β-hexosaminidase, histamine, cysteinyl leukotriene and prostaglandin D2 were observed in RBL2H3 cell line when treated (125 μg) with CP 26 kDa protein. Conclusively, in vivo and in vitro studies revealed the allergenic potential of purified CP 26 kDa protein. Being a potential allergen, plant albumin may play a pivotal role in CP induced allergenicity. Current study will be helpful for better development of therapeutic approaches to prevent the allergenicity in CP sensitized individuals.